On the growth of nucleation mode particles: source rates of condensable vapor in polluted and clean environments - Kulmala, M.; Petäjä, T.; Mönkkönen, P.; Koponen, I. K.; Dal Maso, M.; Aalto, P. P.; Lehtinen, K. E. J.; Kerminen, V.-M. (CCSD, 2005)
International audience The growth properties of nucleation mode particles were investigated. The variation of source rates of condensable vapors in different locations and environmental conditions was analyzed. The measurements were performed in background stations in Antarctica, in Finnish Lapland and Boreal Forest stations (SMEAR I and SMEAR II) as well as in polluted urban sites in Athens, Marseille and New Delhi. Taking advantage of only the measured spectral evolution of aerosol particles as a function of time the formation and growth properties of nucleation mode aerosols were evaluated. The diameter growth-rate and condensation sink were obtained from the measured size distribution dynamics. Using this growth rate and condensation sink, the concentration of condensable vapors and their source rate were estimated. The growth rates and condensation sinks ranged between 0.3-20nmh -1 and 10 -4 -0.07s -1 , respectively. The corresponding source rate of condensable vapors varied more than 4 orders of magnitude from 10 3 to over 10 7 cm -1 s -1 . The highest condensation sink and source rate values were observed in New Delhi and the smallest values in Antarctica.